One-Action in More States: The Propriety of Expanding the Kansas One-Action Rule into Other Jurisdictions - Jaran Moten (Washington University School of Law, 2013)
Most second-year law students who have completed an introductory course on civil procedure can explain the doctrines of issue and claim preclusion—collectively known as res judicata—with some proficiency. By successfully invoking either doctrine, one can avoid having to defend against a prolonged and expensive lawsuit. A defendant who fails to meet the elements of either probably will not be able to preclude a plaintiff‘s action. This is not the case in Kansas. The one-action rule in Kansas prohibits a plaintiff from securing a comparative fault determination and then suing other defendants for injuries arising from negligence related to the same transaction. Developed through a string of judicial interpretations of the Kansas comparative negligence statute, the rule has since been embraced by the legislature and has enjoyed consistent support in Kansas courts. If the Kansas one-action rule furthers all of its justificatory principles— judicial economy, fairness, and consistency, to name a few—why have the courts and, ostensibly, legislatures of other states refused to follow Kansas‘s lead and adopt an identical rule? This Note will begin by providing a brief history of the one-action rule, from its (mostly) judicially created origins to its explicit approval by the Kansas legislature. It will also examine the current status of the doctrine in Kansas, including recent modifications and clarifications. The following part will discuss the rule‘s failure to expand into other jurisdictions that have expressly considered its rationale and implications. The concluding part will analyze the justifications for both supporting and opposing the expansion of the one- action rule and provide possible reasons that the rule has not caught on the way some commentators think it should have. Ultimately, this Note proposes that, at least from a theoretical standpoint, the one-action rule provides an element of fairness that might otherwise be missing from comparative negligence law. But the practical uncertainties underlying the rule‘s application might justify most jurisdictions‘ hesitance to adopt something substantially similar. The rule‘s practical implications should be investigated so that sufficient information exists for jurisdictions to make informed decisions regarding its adoption.
Keywords: Kansas; one-action rule; comparative negligence